(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
The article presents the structural design and principle of operation of the device for wet cleaning of dusty gases with a truncated cone contact element that provides contact between the dusty gas and the liquid. Theoretical studies were carried out and a formula was derived for calculating the total pressure loss in the working chamber of the device depending on the dusty gas flow rates in the working chamber of the device and the resulting local and contact element resistance coefficients. As a result of calculating the total pressure lost by the recommended formula, it is possible to determine the efficiency of dust gas cleaning and the optimal hydrodynamic parameters of the contact elements of the apparatus.